Perempuan, Antara Pendidikan Tinggi Dan Ketenagakerjaan - Soleman, Noviyanti (AL-WARDAH: Jurnal Kajian Perempuan, Gender dan Agama, 2022)
The purpose of this study is to determine the existence of highly educated women in the world of work. This research method is library research. The results of the study state that female labor force participation is high for women with low education, then decreases for women with secondary education, and increases again for women with high levels of education. This is due to several factors including age, wages, and asynchronous between the chosen majors with employment and family factors.